BOOK AS AN ART OBJECT IN 16th CENTURY EUROPE: ON THE BASIS OF 16TH CENTURY BOOKS IN SLOVENIAN LIBRARIES - JERELE, INES (Knygotyra, 2010)
INES JERELENational and University LibraryTurja ka 1, 1000 Ljubljana, SloveniaE-mail: ines.jerele@nuk.uni-lj.siIn the 16th century, printed book becomes a unique designed art work. There is almost no distinction of printed elements in books from the beginning of the 16th century and ones printed in the incunabula period as the thinking about book production was still under the influence of the manuscript tradition. But throughout the 16th century and especially at the end of it, the basic thinking about books changed. The modified role of books in High Renaissance and Mannerism could be seen as a consequence of social and technical changes in society on the one hand and as a reason for the newly born and formatting reading culture on the other. Mass production was at that point primarily introduced to the Western World. In spite of all transformation that our society has been gone through in these past five centuries, some of the basic elements of printed books, which were acknowledged already in the period under study, are still used not only in printed media, but also in other accompanying production. There was a research made on books printed till 1600. Inserted graphic works which are all illustrations, secondary decoration and initials, were analyzed. All books embraced by the research are kept in two Slovenian libraries. However, as Slovenia had almost no printing production of its own in the 16th century, the picture we get from the research can be regarded as an overview of printing production in Renaissance Europe.
Keywords: early prints; High Renaissance; philosophy; aesthetics; illustration; book decoration